Topic Familiarity and Genre Familiarity: Which One Contributes More to Listening Comprehension? - Ovilia, Ririn; Addinna, Ainul (English Department FBS UNP, 2020)
The role of prior knowledge has been acknowledged in realm of English Language Teaching, including teaching Listening. Due to the profound role of prior knowledge, experts and practitioners compromise that the first step of teaching listening is building the students’ prior knowledge. However, there is dilemma which background knowledge has the strongest relationship to students’ listening comprehension, either content schemata (Topic Familiarity) or formal schemata (Genre Familiarity). Therefore, this study aimed at investigating the relationship and contribution of topic and genre familiarity to listening comprehension and eventually determining the better predictor of listening comprehension. Furthermore, fourth semester ELT students at Universitas Negeri Malang who were taking advance listening course participated as the subjects in this study. The findings of this study revealed that the contribution of topic familiarity was significantly higher than genre familiarity. This result also pointed out that topic familiarity was better predictor of listening comprehension.